Gallbladder Agenesis and Cystic Duct Absence in an Adult Patient Diagnosed by Magnetic Resonance Cholangiography: Report of a Case and Review of the Literature - Valeria Fiaschetti; Giovanna Calabrese; Silvia Viarani; Gabriele Bazzocchi; Giovanni Simonetti (Case Reports in Medicine)
Gallbladder agenesis (GA) is a rare congenital anomaly of the biliary system often associated with other congenital abnormalities. Patients become symptomatic in 23% of cases. GA is often misinterpreted as other diseases, therefore, leading to unnecessary surgery. We report a case of congenital GA associated to cystic duct absence and a biliary tract abnormality diagnosed by Magnetic Resonance with Cholangiopancreatography.